Development and evaluation of modified lead gloves to reduce hand radiation dose during interventional radiological procedures - Hyun-Jun Park; Byungdu Jo; Seung-Jae Lee (Nuclear Engineering and Technology, 2024)
We developed lead gloves that minimize radiation dose to the operator's hands during interventional radiological procedures and that do not impede the operator's surgical capabilities. Existing lead gloves can protect the operator's hands by shielding radiation, but use of such gloves may impair preception sensitivity, resulting in a reduction in the operator's surgical ability. Accordingly, in this study, we developed modified lead gloves that can reduce radiation dose while maintaining operator sensitivity during procedures by modifying the operator's main surgical finger area in existing lead gloves. To evaluate the performance of developed modified lead gloves, radiation was applied in surgical conditions without gloves and with surgical gloves, lead gloves, and modified lead gloves. The radiation dose was evaluated for each condition. When the modified lead gloves were worn, the degree of shielding was similar to when conventional lead gloves were worn. Based on these results, if the operator wears modified lead gloves during interventional radiological procedures, they will protect the hands from radiation while maintaining physical sensitivity in the hands.